A one year prospective study of acute renal failure in pregnancy and its maternal and fetal outcome - Kerure, Rajshekhar D.; Biradar, Amaresh; Lakshetty, Swetha; Biradar, Sudha (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2024)
Background: Pregnancy related acute renal failure is still common in developing countries. This study is aimed to evaluate the etiological factors responsible for ARF in pregnancy, and, maternal and fetal outcome of this condition. It contributes upto 20-22% of the referrals to higher centers and is associated with high risk of maternal mortality (9 to 55%) in developing countries. Methods: This is a prospective study carried out at M. R. medical college and Basaweshwara teaching hospital, Kalaburagi (Gulbarga), for one year from January 2017 to December 2017. Results: A total of 38 patients were hospitalised with renal failure in pregnancy. Majority of the patients (73.68%) were multigravida. Eclampsia (42.10%) and severe post-partum hemorrhage (21.05%) were the most common causes of acute renal failure in late third trimester and in post-partum period. Edema (65.78%) and oliguria (50%) were the most common presenting complaints. Most cases (73.68%) responded to diuretics and IV fluids. 21.05% required dialysis, 39.47% needed ICU admissions. Maternal mortality amounted to 13.15%. Fetal IUGR (18.42%), preterm delivery (13.15%), fetal distress (10.52%), NICU admissions (15.78%), and still births (7.89%) were noted. Conclusions: Pregnancy related acute renal failure is still high in developing countries. Good antenatal care, correction of anaemia, early diagnosis and management of pre-eclampsia, good transport facilities to shift to tertiary care centers are essential requirements to reduce maternal and fetal mortality and morbidity due to acute renal failure in pregnancy.